The Use of Environmental DNA as Preliminary Description of Invertebrate Diversity in Three Sicilian Lakes - Manuela Mauro; Francesco Longo; Mario Lo Valvo; Aiti Vizzini; Antonino Di Grigoli; Slobodanka Radovic; Vincenzo Arizza; Luca Vecchioni; Laura La Paglia; Vinicius Queiroz; Marialetizia Ponte; Claudio Gargano; et al. (Animals)
Freshwater ecosystems are among the most severely affected environments by species loss caused by climate change and intense anthropogenic pressure. To preserve biodiversity, biomonitoring plays a key role by providing reliable data on biological diversity and ecological status. Environmental DNA (eDNA) metabarcoding has emerged as a powerful and non-invasive alternative to traditional morphology-based sampling and identification methods. This study represents the first application of eDNA analysis to assess the invertebrate communities in three Sicilian Lakes: Poma, Piana degli Albanesi and Scanzano. Water samples were collected at two points in each lake and after filtration with nitrocellulose membranes, eDNA was extracted and metabarcoding analysis was performed. A total of 27 species were identified, belonging to Phyla of Annelida, Arthropoda and Rotifera. Notably, the analysis revealed the presence of alien species (Daphnia parvula and Acanthocyclops americanus), a dangerous species associated with the transmission of viral diseases (Culex pipiens), and potential new records for Sicily (Stylaria lacustris, Platypalpus exilis, Pammene aurana, Limnephilus rhombicus). These results provide a preliminary snapshot of invertebrate biodiversity at these sites, demonstrating how eDNA has the potential to complement, but not replace, traditional methods, contributing to the assessment of ecosystem status.